Temporomandibular disorders and Burnout syndrome in students of the eighth period of dentistry course - Laís Valencise MAGRI; Melissa de Oliveira MELCHIOR; Larissa JARINA; Flávia Fanchiotti SIMONAGGIO; César BATAGLION (RGO: Revista Gaúcha de Odontologia, 2019)
Objective: To investigate the incidence of painful temporomandibular disorders (TMD) and Burnout Syndrome (BS) in Dentistry students, based on the subjective perception of signs and symptoms, and to verify if there is a coexistence relation between these conditions. Methods: 57 students (8th period of the dentistry course, 23 years mean age), 39 women and 18 men, responded to the Maslach Burnout Inventory Questionnaire – Students Survey (MBI-SS), ProTMDMulti and were evaluated for the presence of TMD diagnosis (DC/TMD). Results: The incidence of TMD was 22% and BS was 8.7%. Among the students with BS, 80% had a TMD diagnosis, as well as a greater subjective perception of TMD signs and symptoms and a longer duration of pain. They also showed higher scores of signs/symptoms perception for situations involving orofacial function. Conclusion: There seems to be a clinical coexistence between the BS and painful TMD in the studied sample, Dentistry students with BS and high scores on the MBI-SS are more likely to have painful TMD.